2013
DOI: 10.1002/hbm.22361
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric differences of fMRI responses to visual stimuli in patients with side‐fixed migraine aura

Abstract: Migraine sufferers with aura often report photosensitivity and visual discomfort outside of attacks and many consider bright or flickering light an attack-precipitating factor. The nature of this visual hypersensitivity and its relation to the underlying pathophysiology of the migraine aura is unknown. Using fMRI measurements during visual stimulation we examined the visual cortical responsiveness of patients with migraine with aura. We applied a within-patient design by assessing functional interhemispheric d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 54 publications
6
76
1
Order By: Relevance
“…A better understanding of these mechanisms is crucial for the much-needed improvement of prophylactic treatment. Functional magnetic resonance imaging (fMRI) studies have shown hyperresponsiveness of visual cortical areas in migraine patients with aura interictally [6][7][8]. These symptoms clearly originate from the cerebral cortex [4].…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of these mechanisms is crucial for the much-needed improvement of prophylactic treatment. Functional magnetic resonance imaging (fMRI) studies have shown hyperresponsiveness of visual cortical areas in migraine patients with aura interictally [6][7][8]. These symptoms clearly originate from the cerebral cortex [4].…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal hyperexcitability has already been implicated in a number of phenomena related to discomfort glare, such as: visual discomfort (Haigh et al, 2013;Juricevic et al, 2010), photophobia (Boulloche et al, 2010;Denuelle et al, 2011) and light-induced migraine (Coutts et al, 2012;Hougaard et al, 2014). For example, using positron emission topography (PET), Boulloche and colleagues (Boulloche et al, 2010) found increased bilateral activity in the visual cortex (specifically the cuneus, lingual gyrus and posterior cingulate cortex) in migraineurs with photophobia at multiple light levels.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies using visual stimulation BOLD fMRI paradigms have detected hyper-responsiveness in striate areas during visual stimulation in interictal MwA [17,48] as well as more brain activation in the visual functional network including the inferior frontal gyrus and the inferior and superior parietal lobule, all regions involved with attention orienting and oculomotor control (Hougaard and colleagues 2014) [18]. Although results of a smaller study by Bridge et al (2015) [49•] did not find differences in striate cortex activation between MwA and MwoA, the authors demonstrated decreased GABA levels in the occipital cortex and a positive relationship between BOLD-signal change and occipital glutamate/ creatine ratios using magnetic resonance spectroscopy (MRS).…”
Section: Migraine and Auramentioning
confidence: 97%
“…These studies have implicated common regions that show more activation or hyperactivation between attacks (interictally) in migraineurs relative to healthy controls during sensory processing. These include prefrontal, parietal (postcentral/primary somatosensory gyrus), temporal (temporal pole, fusiform, hippocampus, parahippocampal gyrus) cortex, and subcortical regions (cingulate, thalamic complex) [14][15][16][17][18]. Regions where migraineurs show less interictal activation or hypoactivation relative to healthy controls include areas of the brainstem (pons, medulla) and temporal and parietal (secondary somatosensory) cortex [15,[19][20][21].…”
Section: Introductionmentioning
confidence: 98%